A generalized solid strengthening rule for biocompatible Zn-based alloys, a comparison with Mg-based alloys. Issue 40 (8th October 2019) - Guo, Yuanqi; Zhang, Shihao; Wei, Bo; Legut, Dominik; Germann, Timothy C.; Zhang, Haijun; Zhang, Ruifeng
Abstract : A general strategy for designing biocompatible Zn-based alloys by means of the ab initio informed Peierls–Nabarro model and solid-solution strengthening model. Abstract : Solid solution strengthening has been widely used in designing various high-performance biocompatible Mg-based alloys, but its transferability to other biocompatible metals such as Zn-based alloys is questionable or nearly absent. In the present study, an ab initio informed Peierls–Nabarro model and Leyson et al. 's strengthening model are used for a systematic investigation on solute strengthening in Zn-based alloys, which is compared with the widely studied Mg-based alloys. Although an inverse relationship was revealed between volume misfit ε b and chemical misfit ε SFE for both Zn-based and Mg-based alloys, most solutes would however result in positive ε b and negative ε SFE for Zn-based alloys, differing from Mg-based alloys. With ε b and ε SFE as two key descriptors, a generalized scaling diagram is finally drawn for a fast evaluation of solid solution strengthening in Zn-based alloys, indicating that the alkaline-earth and rare earth elements are better strengtheners for Zn-based alloys, which provides a general rule in designing novel biocompatible materials.